2012
DOI: 10.1007/s10404-012-0943-5
|View full text |Cite
|
Sign up to set email alerts
|

Rotational regimes of freely suspended liquid crystal films under electric current in presence of an external electric field

Abstract: The electrohydrodynamic (EHD) vortices produced by an electric current in freely suspended liquid crystal (LC) films of N-(4-methoxybenzylidene)-4-butylaniline (MBBA), convert to a pure rotation in the presence of external electric field (E ext ) perpendicular to the current direction. Here, the direction and strength of the rotation are precisely under control by our self-made device called ''liquid-film motor''. In this paper, we present experimental observations of the EHD fluid flow when external electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…This magneto-hydrodynamic method of inducing ow in a conducting uid has a wide range of applications in microuidics and microchemistry and has been studied by different groups for various purposes. 5,[25][26][27][28][29] Along the same direction, in this paper, we extend our previous study (electrically-induced rotation [17][18][19] ) by investigating rotations induced by uniform and non-uniform magnetic elds in conducting uids carrying electric current. We look for different congurations in which an applied electric/magnetic eld in the presence of an electric current results in generation of vorticity in an incompressible uid.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…This magneto-hydrodynamic method of inducing ow in a conducting uid has a wide range of applications in microuidics and microchemistry and has been studied by different groups for various purposes. 5,[25][26][27][28][29] Along the same direction, in this paper, we extend our previous study (electrically-induced rotation [17][18][19] ) by investigating rotations induced by uniform and non-uniform magnetic elds in conducting uids carrying electric current. We look for different congurations in which an applied electric/magnetic eld in the presence of an electric current results in generation of vorticity in an incompressible uid.…”
mentioning
confidence: 56%
“…Morris et al 15,16 suggested that it is the electric charges accumulated on the surface of suspended lms that produce such instabilities. Amjadi et al [17][18][19] proposed a method for controlling the rotational ow on thin suspended liquid lms demonstrating that a simultaneous application of an electric eld and an electric current produces controllable rotations in a suspended liquid lm. Such an instability has been studied theoretically by Liu et al 20,21 and Nasiri et al 22 and the rotation mechanism was explained by Feiz et al using a thin lm electro-convection model.…”
Section: -9mentioning
confidence: 99%
“…In this context, we have previously introduced a device called the liquid film motor (LFM) [31][32][33]. The device was consisted of a horizontal two dimensional frame on which a suspended liquid film is formed, connected to a pair of conducting electrodes which conduct an electric current through it.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are based on the use of thermal gradients, 12,13 magnetic fields, 14,15 or electromechanical means such as piezoelectric actuators. 16 Many such experiments require fluid rotation 10,17,18 that itself requires mechanisms such as using AC and DC electric fields [19][20][21] or a magnetic field and a magnetic probe 17 to rotate a thin liquid film. A polar fluid, connected to a low DC voltage and high electric field, experiences a torque caused by the electric field maintenance of the equilibrium in polarization.…”
mentioning
confidence: 99%
“…19,20 The controllable rotation of a fluid film has also been reported for polar liquid films 19,20 and MBBA liquid crystal films. 21 In all of these cases, the rotation of a thin suspended film of fluid was studied. In this paper, we report a purely electrically driven rotation in bulk of a polar liquid such as water.…”
mentioning
confidence: 99%